An approach for the synthesis of nakamuric acid. Issue 22 (3rd June 2015) - Wang, Xiaolei; Chen, Chuo
Abstract: The biosynthesis of dimeric pyrrole–imidazole alkaloids is likely mediated by enzyme-catalyzed reversible single-electron transfer (SET) cycloaddition. We now show that Ir(ppy)3 can promote SET-mediated formal [2+2] and [4+2] cycloaddition reactions of pyrrole–imidazole alkaloids-related substrates under photolytic conditions. This biomimetic approach is useful for the construction of the core skeleton of nakamuric acid and sceptrin. Graphical abstract: